2015
DOI: 10.4049/jimmunol.1402735
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cells Maintain Local Tissue Tolerance in a Model of Systemic Autoimmune Disease

Abstract: Systemic autoimmune diseases such as lupus affect multiple organs, usually in a diverse fashion where only certain organs are affected in individual patients. It is unclear whether the ‘local’ immune cells play a role in regulating tissue specificity in relation to disease heterogeneity in systemic autoimmune diseases. Here, we used skin as a model to determine the role of tissue-resident dendritic cells in local and systemic involvement within a systemic lupus disease model. Skin-resident dendritic cells, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…We also used MRL/Mp-Fas mice treated with Poly IC. MRL/Mp-Fas mice at 12–17 weeks of age develop multiple autoimmune disorders, including lupus, glomerulonephritis and AIP 34 . Figure 4f shows modest infiltrate in the pancreas of 14 weeks old MRL/Mp-Fas mice that was reduced by treatment with C18 (4 mice).…”
Section: Resultsmentioning
confidence: 99%
“…We also used MRL/Mp-Fas mice treated with Poly IC. MRL/Mp-Fas mice at 12–17 weeks of age develop multiple autoimmune disorders, including lupus, glomerulonephritis and AIP 34 . Figure 4f shows modest infiltrate in the pancreas of 14 weeks old MRL/Mp-Fas mice that was reduced by treatment with C18 (4 mice).…”
Section: Resultsmentioning
confidence: 99%
“…At low levels of antigen presentation, LCs induce expansion of skin-resident memory Treg cells that suppress autologous T-cell responses locally. 5,46 However, once a threshold of antigen is surpassed, the role of LCs is switched to favor effector T RM cells (Foxp3 lo , CD127 1 ), with activation, proliferation, and production of the effector cytokines IFN-g and IL-17. 5 In addition to driving tolerance at the site of antigen detection, studies in mice have shown that skin-resident DCs migrate from their cutaneous location and induce antigen-specific generation of Foxp3 1 Treg cells in LNs.…”
Section: Mechanisms Of Immune Tolerance Through Lcs and T Cellsmentioning
confidence: 99%
“…3,6,7 LCs also play a role in generation of IL-10-producing Foxp3 1 Treg cells. 5,46 IL-10 in turn inhibits macrophage function, downregulates MHCII and costimulatory molecules, decreases proinflammatory cytokines, and directs DCs toward a tolerogenic phenotype. 124 Notably, IL-10-deficient mice develop colitis.…”
Section: Mechanisms Of Immune Tolerance Through Lcs and T Cellsmentioning
confidence: 99%
“…To assess the role of LCs in immune tolerance in the skin, a group crossed systemic lupus erythematosus mice (MRL-lpr and MRL/MpJ-Fas +/+ ) which develop a syndrome that resembles lupus in humans, with B6 mice, in which the LC-specific gene CD207 (Langerin) is attached to the diphtheria toxin (DT) receptor, and a single dose of DT temporarily abates Langerin+Langerhans cells [28]. Mouse serum showed skin self-antigens (Dsg-3), and cells isolated from these mice displayed an immune response when cultured with Dsg-3.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse serum showed skin self-antigens (Dsg-3), and cells isolated from these mice displayed an immune response when cultured with Dsg-3. The authors conclude that autoimmune-prone mice, LCs are capable of protecting mice from acquiring autoimmune dermatitis, and maintaining skin tolerance [28]. …”
Section: Introductionmentioning
confidence: 99%